In-Frame Variants in STAG3 Gene Cause Premature Ovarian Insufficiency - Xiao, Wen-Juan; He, Wen-Bin; Zhang, Ya-Xin; Meng, Lan-Lan; Lu, Guang-Xiu; Lin, Ge; Tan, Yue-Qiu; Du, Juan (Frontiers in Genetics, 2019)
Premature ovarian insufficiency (POI) is a severe clinical syndrome defined by ovarian dysfunction in women less than 40 years old who generally manifest with infertility, menstrual disturbance, elevated gonadotrophins, and low estradiol levels. STAG3 is considered a genetic aetiology of POI, which facilitates entry of REC8 into the nucleus of a cell and plays an essential role in gametogenesis. At present, only six truncated variants associated with POI have been reported; there have been no reports of an in-frame variant of STAG3 causing POI. In this study, two novel homozygous in-frame variants (c.877_885del, p.293_295del; c.891_893dupTGA, p.297_298insAsp) in STAG3 were identified in two sisters with POI from a five-generation consanguineous Han Chinese family. To evaluate the effects of these two variants, we performed fluorescence localization and co-immunoprecipitation analyses using in vitro cell model. The two variants were shown to be pathogenic, as neither STAG3 nor REC8 entered nuclei, and interactions between mutant STAG3 and REC8 or SMC1A were absent. To the best of our knowledge, this is the first report on in-frame variants of STAG3 that cause POI. This finding extends the spectrum of variants in STAG3 and sheds new light on the genetic origins of POI.